2011
DOI: 10.1002/arch.20456
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and gene expression of apolipophorin III from the ghost moth, Thitarodes pui (Lepidoptera, Hepialidae)

Abstract: Apolipophorin III (apoLp-III) functions in lipid transport and immune activation in insects. We cloned a cDNA encoding putative apoLp-III from larvae of Thitarodes pui, a host species of Ophiocordyceps sinensis, with great economic importance in the Tibetan Plateau. Excluding a putative signal peptide of the first 20 amino acid residues, the 171-residue mature apoLp-III has a calculated molecular mass of 18,606 Da. T. pui apoLp-III shares little sequence homologies (<36%) with other apoLp-IIIs. Phylogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Third, T. pui is a member of the primitive lepidopteran family Hepialidae (Hebert et al, 2003) and has a long evolution distance in relation to other lepidopteran insects. For example, phylogenetic analysis clustered the heat shock proteins, beta-1,3-glucan recognition proteins, and apolipophorin III proteins of T. pui into a new clade or formed a distinct diverging branch, respectively Zou et al, 2011;Sun et al, 2012). Thus, sequence divergences between T. pui and other lepidopteran species is relatively large, which may have led to the low percentage of matches in the species distribution results.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…Third, T. pui is a member of the primitive lepidopteran family Hepialidae (Hebert et al, 2003) and has a long evolution distance in relation to other lepidopteran insects. For example, phylogenetic analysis clustered the heat shock proteins, beta-1,3-glucan recognition proteins, and apolipophorin III proteins of T. pui into a new clade or formed a distinct diverging branch, respectively Zou et al, 2011;Sun et al, 2012). Thus, sequence divergences between T. pui and other lepidopteran species is relatively large, which may have led to the low percentage of matches in the species distribution results.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Oligonucleotide primers for qRT-PCR were designed using Primer3web version 4.0.0 (http://primer3.ut.ee/) and are detailed in Supplementary Sun et al, 2012). All quantitative PCR runs were repeated in 3 replications.…”
Section: Experimental Validationmentioning
confidence: 99%
“…and/or other posttranslational processing of the mature apoLp-III. Since the fat body is the major site of apoLp-III synthesis in insects [17,19,21,23,39,41] and presence of different apoLp-III forms was demonstrated by us in G. mellonella fat body (this report), it can be suggested that additional apoLp-III forms detected in the hemolymph are generated during and/or after release of apoLp-III from the fat body cells into the hemolymph. Many proteins synthesized as inactive precursors are subjected to limited proteolysis by specific proteases to form their final active structures.…”
Section: Discussionmentioning
confidence: 73%
“…An increase in apoLp‐III transcripts was observed in T. molitor infected with intracellular pathogen Listeria monocytogenes after 24–72 h. In the same insect, immunization with E. coli caused an increase in apoLp‐III expression 24–72 h after the challenge but no increase was observed 12 h after challenge (Noh et al., ). Upregulation of apoLp‐III expression, followed by its decrease at later time‐points was observed in Thitarodes pui after infection with fungus Beauveria bassiana (Sun et al., ). On the other hand no change in apoLp‐III expression was observed in infected Anopheles gambiae (Mendes et al., ).…”
Section: Discussionmentioning
confidence: 98%